1985
DOI: 10.1099/0022-1317-66-10-2199
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Expression of the Immediate-Early Protein of Herpesvirus Saimiri in Populations of Productively Infected Cells

Abstract: SUMMARYThe time course of virus replication in cultures of permissive cells infected with high multiplicities of herpesvirus saimiri (HVS), a gammaherpesvirus, is protracted relative to the replication of herpes simplex virus (HSV), an alphaherpesvirus, under similar conditions. The basis for this difference was investigated by quantitative immunofluorescence microscopy exploiting monoclonal antibodies specific to the HVS 52000 mol. wt. immediate-early polypeptide (IE 52K) and to delayed-early (DE 51K, DE 110K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…This proportion changed from 10 to 20~ at 6 h in the presence of cycloheximide to 40 to 509/00 at 12 h. In the absence of cycloheximide only a very low level of hybridization was visualized with the EcoRI-I probe. These results of in situ hybridization to measure RNA accumulation resemble very closely the results from studies reported by Randall et al (1985) of the asynchronous accumulation of the 52K protein based on immunofluorescence microscopy.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…This proportion changed from 10 to 20~ at 6 h in the presence of cycloheximide to 40 to 509/00 at 12 h. In the absence of cycloheximide only a very low level of hybridization was visualized with the EcoRI-I probe. These results of in situ hybridization to measure RNA accumulation resemble very closely the results from studies reported by Randall et al (1985) of the asynchronous accumulation of the 52K protein based on immunofluorescence microscopy.…”
supporting
confidence: 78%
“…Thus, in addition to cell-to-cell variations in entry and intracellular processing of virus particles which provides one component of asynchrony (Randall et al, 1985), it is now clear that the transcription of the IE 52K gene requires (or is prevented by) factors which do not affect the transcription of the IE gene in HindlII-G. Thus there is differential regulation of the expression of these two IE genes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…At high multiplicities of infection (10 post-infection (data not shown; Randall et al, 1985). The number of loci in which ICP 4 and ICP 8 accumulated per nucleus was dependent on the multiplicity of infection ( Fig.…”
Section: Intranuclear Localization Of Icp 4 Icp 8 Dna Polymerase Anmentioning
confidence: 99%